Medical security and catastrophic health expenditures among households containing persons with disabilities in Korea: a longitudinal population-based study. Issue 1 (December 2016) - Choi, Jae; Shin, Jae-Yong; Cho, Kyung-Hee; Nam, Jin-Young; Kim, Ju-Young; Lee, Sang
Abstract Background Although persons with disabilities need access to comprehensive and consistent healthcare services, a significant number of the poor with disabilities do not receive Medical-Aid due to the conditions of eligibility. We aimed to compare the financial burden of healthcare services between two groups of poor persons with disabilities: those not enrolled in Medical-Aid and Medical-Aid enrollees. Methods This study used the 1st–8th data (2008–2014 year) of Panel Survey of Employment for the Disabled (PSED) conducted by the Korea Employment Agency for the Disabled. We classified adults who did not exceed 100 % of the poverty level into two groups (N = 3, 010). The first group consisted of enrollees in Medical-Aid (n = 1, 259) and the second group comprised those not enrolled in Medical-Aid (n = 1, 325). We applied generalized estimating equations (GEEs) to assess the independent effect of enrollment in Medical-Aid on catastrophic health expenditures (CHE). Results We found that about 4.2 % of the poor not enrolled in the Medical-Aid experienced CHE and the poor not enrolled in Medical-Aid were 2.1 times more likely to experience CHE than Medical-Aid enrollees after applying multivariate models adjusted for several covariates. Conclusions Given the additional expenses for treatment and rehabilitation caused by disability-related health problems, persons with disabilities are more likely to face barriers to needed medical services. Thus, policy makers need to expand the number of people receiving Medical-Aid by loosening the strict criteria for those with disabilities.